Pengaruh Pemberian Obat Asam Folat, Eritropoietin dan Kombinasi Asam Folat Eritropoietin dalam Meningkatkan Hemoglobin pada Pasien Hemodialisa di RSUD dr. Gunawan Mangunkusumo - Purnami, Islina Dewi; Indriani, Yonanda Pratiwi; Susilowati, Dwi Retna (Sultan Agung Islamic University of Semarang, 2024)
Background: Anemia is a decrease in the total amount of hemoglobin or the number of red blood cells which causes insufficient oxygen supply to meet the body's physiological needs. This study aim to determine the effect of administration of folic acid, erythropoietin (hemapo) and erythropoietin folic acid combinations in increasing hb in hemodialysis patients at RSUD dr. Gunawan Mangunkusumo. Methods: This research is a non-experimental study using a cross-sectional design. Data collection was carried out retrospectively using medical records taken at the medical record unit which received treatment therapy with folic acid, erythropoietin and erythropoietin folate combination in outpatient hemodialysis patients. The sampling technique was carried out by purposive sampling technique. Data obtained during the study were analyzed using the Paired T-test (p-Value = <0.05). Results: Based on the Paired T-Test analysis, it is known that the p-Value = 0.001, this indicates that there is a significant difference in changes in hemoglobin levels before and after consuming folic acid, erythropoietin (hemapo), and the combination of increased Hb in hemodialysis patients at RSUD dr. Gunawan Mangunkusumo. Conclusion: The results of research that has been conducted usingOthe Paired T-Test show that there is a significant difference in changes in hemoglobin levels before and after consuming folic acid, erythropoietin (hemapo), and the combination in increasing Hb in patients at RSUD dr. Gunawan Mangunkusumo.